Retrospective analytical six months study of vascular abnormalities of brain - Chelliah, Nellaiappan (International Journal of Advances in Medicine, 2017)
Background: Vascular abnormalities of brain include vessel obstruction, vascular tumours, vascular malformations and congenital anomalies. In this study, vascular abnormalities reported in our institute are analysed retrospectively. Methods: This is a retrospective analytical study of six months period from May 2015 to October 2015. The study was done in the radiodiagnosis department of Tirunelveli Medical College Hospital. 702 cases of MRI brain scans have been taken in above period for various conditions. In which Patients with vascular abnormalities in the scan were selected for the study i.e sample selection. No of patients selected for analysis are 60. Those findings were analysed and hereby are presented, in which age varied as low as 1 year and as high as 75 years. Results: From this study, it is noted that most of vascular abnormalities become symptomatic between the ages of 21-40. Out of that most of patients lie in age group of 21-30. There is no significant difference seen in the gender distribution of the total vascular abnormalities. Vascular abnormalities of brain are common imaging findings. Radiology plays major role in diagnosing these conditions. Rare cases like Vein of galen ectasia, aplasia of right internal carotid artery are diagnosed in above patients. Conclusions: On analysis it is noted that CT scan was able to pick up forty percentage of vascular abnormality cases. MRI is able to pick up even congenital anatomical variations and subtle pathologies. Radiology plays major role in diagnosing vascular abnormalities of brain. CT and MRI complement each other in diagnosis. Parenchymal AVM should be ruled out when there is ectasia of vein of galen. CT of base of skull gives information regarding carotid canal in absent carotid artery cases. Pituitary gland changes should be noted in cases of absent carotid artery.